2017
DOI: 10.1038/s41598-017-02338-3
|View full text |Cite
|
Sign up to set email alerts
|

The rice production practices of high yield and high nitrogen use efficiency in Jiangsu, China

Abstract: To face the great challenges of ensuring food security and environmental sustainability, agricultural production must be improved by high yield and high resource utilization efficiency (HYHE). We recently addressed this challenge and evaluated yield potential by surveying 735 farmers in 2008–2012 and then conducting 6 rice field experiments in 2008–2013 with large demonstration areas in 2010–2013 aimed to actualize the HYHE in Jiangsu Province, China. The survey result showed that the averaged N rate, grain yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 54 publications
2
45
1
1
Order By: Relevance
“…In this study, the validation data further showed the optimum N fertilizer rate (264 ∼ 272 kg N ha −1 ) was similar to N2 (270 kg N ha −1 ). However, local rice farmers in our study area (Jiangsu province, China) usually applied N fertilizer at levels (337 kg N ha −1 ) closer to N3 (Guo et al., ; Peng et al., ). The NFOA and NNI approaches are not superior entirely in yield, N use efficiency, and financial outcomes compared with the fixed‐time N management under fewer N conditions, but those types of easily operated and reliable N regulation methods are critical for high‐efficiency and sustainable agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the validation data further showed the optimum N fertilizer rate (264 ∼ 272 kg N ha −1 ) was similar to N2 (270 kg N ha −1 ). However, local rice farmers in our study area (Jiangsu province, China) usually applied N fertilizer at levels (337 kg N ha −1 ) closer to N3 (Guo et al., ; Peng et al., ). The NFOA and NNI approaches are not superior entirely in yield, N use efficiency, and financial outcomes compared with the fixed‐time N management under fewer N conditions, but those types of easily operated and reliable N regulation methods are critical for high‐efficiency and sustainable agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…The mean annual temperature is 15.9 • C and the mean annual precipitation varies from 781-1382 mm [33]. The properties of the top layer soil (0-20 cm) in Jiangsu are as follows: organic matter, 21.65-24.73 g kg −1 ; total N, 1.15-1.61 g kg −1 ; Olsen-P, 12.95-15.74 mg kg −1 ; NH 4 OAc-K, 89.51-141.11 mg kg −1 ; and pH, 6.54-7.46 [34].…”
Section: Site Description and Data Collectionmentioning
confidence: 99%
“…A total of 1505 samples were selected for analysis (2008, n = 128; 2009, n = 434; 2010, n = 60; 2011, n = 301; 2012, n = 250; 2013, n = 90; 2014, n = 242). Based on the data of from 2008 to 2012 in the early stage of our laboratory [34], combined with the later survey data and literature collective data, the analysis of yield and NUE gaps is carried out in this study. Households were selected randomly in Jiangsu, China.…”
Section: Site Description and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, using the average yield of 2 years of experimentation, the partial factor productivity and nitrogen agronomic efficiency were calculated through the formulae given by Guo et al (2017) and yield contribution of nitrogen was calculated through the formula given by Tian et al (2017).…”
Section: Yield and Yield-related Parametersmentioning
confidence: 99%